2019
DOI: 10.1186/s12866-019-1550-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CMY-2-type beta-lactamase-producing Escherichia coli isolated from chicken carcasses and human infection in a city of South Brazil

Abstract: Background Food-producing animals, mainly poultry, have been associated with the maintenance and dissemination of antibiotic-resistant bacteria, such as plasmid-mediated AmpC (pAmpC)-producing Enterobacteriaceae, to humans, thus impacting food safety. Many studies have shown that Escherichia coli strains isolated from poultry and humans infections share identical cephalosporin resistance, suggesting that transmission of resistance from poultry meat to humans may occur. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
2
21
1
Order By: Relevance
“…The presence of AmpC genes ( bla CMY-2 , bla DHA-1 , and bla ACC ) [ 18 ] and MBLs genes ( bla IMP , bla VIM , and bla NDM ) [ 19 ] was detected by polymerase chain reaction (PCR). Genomic DNA extraction was performed using the boiling method [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The presence of AmpC genes ( bla CMY-2 , bla DHA-1 , and bla ACC ) [ 18 ] and MBLs genes ( bla IMP , bla VIM , and bla NDM ) [ 19 ] was detected by polymerase chain reaction (PCR). Genomic DNA extraction was performed using the boiling method [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first plasmid-mediated qAmpC, named CMY-1, was described in South Korea (1989). Recent studies have described an increase in specific qAmpC enzymes among hospital or community infections caused by Enterobacteriaceae [ 17 , 18 ]. The DHA-1 and CMY-2 variants are the most common qAmpC types among Enterobacteriaceae implicated in human infections in Portugal [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DHA-1 and CMY-2 variants are the most common qAmpC types among Enterobacteriaceae implicated in human infections in Portugal [ 18 ]. During the last years, the CMY-2 enzyme has been increasingly reported in humans and animals, frequently associated with lineages ST429, ST354 or ST57, among others [ 17 , 19 , 20 , 21 ]. According to recent studies in Portugal, qAmpC-producing E. coli was reported (CMY-2) among sick pets, mostly associated with ST648 [ 6 ], and among healthy humans, associated with lineages ST4953 and ST665 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, these two clones (Ec480-ST361 and Ec481-ST23) had CMY-42. On the other hand, E. coli ST12 with CMY-2 was reported in poultry in Italy [ 71 ], E. coli ST350 in chicken carcasses in Brazil [ 72 ], E. coli ST101 with CMY-42 was described in a paediatric patient with bacteraemia [ 69 ] and E. coli ST1284 with CMY-2 in a dog with skin and soft tissue infection [ 73 ]. Due to the diversity of ST found in this study and those reported in other studies, the dissemination of CMY enzymes seems not to be related to a specific lineage of E. coli , but rather to the transfer of mobile genetic elements.…”
Section: Discussionmentioning
confidence: 99%